(untitled) (Analytical Methods for Drug Development, 2025)
Author Dr. Nirmala Dasari Associate Professor, Dept of Pharmaceutics, Malla Reddy College of Pharmacy, Maisammaguda, Dhulapally, Secunderabad, Telangana, India Abstract Evidence-based medicine involves systematic research evaluation with clinical expertise for optimal patient care. The hierarchy of evidence ranges from meta-analyses and randomized controlled trials to case reports and expert opinions, each with distinct strengths and limitations. Critical appraisal skills enable evaluation of study validity, results significance, and clinical applicability. The GRADE approach provides a systematic framework for rating evidence quality and recommendation strength based on study design, execution, consistency, directness, and precision. Implementation strategies incorporate evidence synthesis into clinical workflows through standardized protocols, decision support tools, and continuous quality assessment mechanisms. Barriers to evidence implementation include resource limitations, knowledge gaps, and organizational constraints, necessitating targeted interventions for successful integration into practice. Keywords: Evidence hierarchy, Critical appraisal, GRADE methodology, Clinical implementation, Research evaluation VIEW PDF